Bringing rigor to evaluations of large-scale programs to improve infant and young child feeding and nutrition: The evaluation designs for the Alive & Thrive initiative - Menon, Purnima; Rawat, Rahul; Ruel, Marie T. (SAGE Publications, 2013)
The evidence base on the impact of large-scale infant and young child feeding (IYCF) and nutrition programs is limited, partly due to the challenges of rigorously evaluating complex programs including multiple interventions.To describe the process used to design Alive & Thrive's impact evaluations in the three target countries and discuss the feasibility of developing contextually relevant designs adapted to the country-specific programmatic context.The evaluation designs for Alive & Thrive needed to address several challenges. These included the selection of intervention components to evaluate rigorously; the identification of appropriate comparison groups in the context of rapidly scaling-up programs; the choice of impact indicators; addressing measurement challenges related to evaluating the impact of interventions targeted during the first 2 years of life on stunting; and developing methods and tools to assess implementation, utilization, and program impact pathways within evolving program portfolios.In Bangladesh and Vietnam, cluster-randomized probability designs are used for the impact evaluations; in Ethiopia, the impact evaluation uses an adequacy design. In all three countries, repeated cross-sectional surveys, 4 years apart, are used to measure impact, and appropriate age groups are sampled separately to capture change in the main impact indicators. In addition, theory-driven process evaluations are used to study factors that facilitate or prevent achievement of impact and scale.We conclude that robust impact and process evaluations of complex, large-scale nutrition programs are feasible, but that early implementer—evaluator engagement and shared vision and motivation to establishing meaningful evaluations are essential.